KONSEP PEMIKIRAN HUKUM DALAM ISLAM - Muhammad Irfan Jufri; Indo Santalia Indo Santalia (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
The purpose of this research is to find out the concept of legal thought in Islam comprehensively and in detail. The research method used is library research. Data collection techniques were derived from various literatures and then used a normative descriptive approach and were analyzed according to the problems related to the theme and title of the study. The results of his research are the concepts, products, characteristics, sources, and principles of the development of Islamic legal thought.